2021
DOI: 10.1002/ajim.23270
|View full text |Cite
|
Sign up to set email alerts
|

Verifying earplug attenuation and evaluating the effectiveness of one‐on‐one training along with earplug fit testing at nine facilities in China

Abstract: Background The purpose of this study was twofold: (1) to measure the personal attenuation ratings (PARs) in Chinese workers wearing hearing protection devices (HPDs), to evaluate the effectiveness of the single number rating (SNR), the noise reduction rating (NRR), and the associated derated values of earplugs; and (2) to evaluate the effectiveness of one‐on‐one training along with earplug fit testing on PAR improvement. Methods Noise exposure measurements, one‐on‐one training, and fit tests to measure earplug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Similar to other findings, the results in this QI project demonstrated that HPD fit testing was an effective method for training employees to properly insert HPDs (Federman & Duhon, 2016; Federman et al, 2021; Gong et al, 2019, 2021; Murphy et al, 2016; Sayler et al, 2018; Smith et al, 2014). In addition, this project showed that an evidence-based practice (i.e., using HPD fit testing to validate expert-fitted HPDs followed by participant return demonstration of self-fit using muscle memory to replicate proper fit) outlined by Federman and Duhon (2016) could be successfully implemented by staff in an occupational health clinic.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Similar to other findings, the results in this QI project demonstrated that HPD fit testing was an effective method for training employees to properly insert HPDs (Federman & Duhon, 2016; Federman et al, 2021; Gong et al, 2019, 2021; Murphy et al, 2016; Sayler et al, 2018; Smith et al, 2014). In addition, this project showed that an evidence-based practice (i.e., using HPD fit testing to validate expert-fitted HPDs followed by participant return demonstration of self-fit using muscle memory to replicate proper fit) outlined by Federman and Duhon (2016) could be successfully implemented by staff in an occupational health clinic.…”
Section: Discussionsupporting
confidence: 83%
“…Time to conduct fit testing varies by system and with the number of trials an individual needs to achieve appropriate PAR. Time to complete fit testing using FitCheck Solo™ in this project was comparable to other studies using this system showing minimum time of 5 minutes for baseline testing and maximum of 30 minutes for up to four fit tests (Gong et al, 2021; Michael and Associates, n.d.; Murphy et al, 2016). Considering cost of equipment, personnel and time, the cost–benefit ratio for a 20% improvement in participants who achieved target PAR appears worthwhile.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations